Perchlorate reduction in microbial electrolysis cell with polyaniline modified cathode. (February 2015) - Li, Jia-Jia; Gao, Ming-Ming; Zhang, Gang; Wang, Xin-Hua; Wang, Shu-Guang; Song, Chao; Xu, Yan-Yan
Graphical abstract: Highlights: Excellent perchlorate reduction was obtained in a non-membrane MEC. PANI-cathode is conductive to the formation of biofilm. The biofilm mainly facilitated electron transfer from cathode to electrolyte. Pili-like were prone to formation with cathode as sole electron donor. Abstract: Excellent perchlorate reduction was obtained under various initial concentrations in a non-membrane microbial electrolysis cell with polyaniline (PANI) modified graphite cathode as sole electron donor. PANI modification is conducive to the formation of biofilm due to its porous structure and good electrocatalytic performance. Compared with cathode without biofilm, over 12% higher reduction rates were acquired in the presence of biocathode. The study demonstrates that, instead of perchlorate reduction, the main contribution of biofilm is involved in facilitate electron transfer from cathode to electrolyte. Interestingly, hairlike structure, referred as to pili-like, was observed in the biofilm as well as in the electrolyte. Additionally, the results show that pili were prone to formation under the condition of external electron field as sole electron donor. Analysis of microbial community suggests that perchlorate reduction bacteria community was most consistent with Azospiraoryzae strain DSM 13638 in the subdivision of the class Proteobacteria .